2018
DOI: 10.3389/fonc.2018.00606
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into SND1 Oncogene Promoter Regulation

Abstract: The staphylococcal nuclease and Tudor domain containing 1 gene (SND1), also known as Tudor-SN, TSN or p100, encodes an evolutionarily conserved protein with invariant domain composition. SND1 contains four repeated staphylococcal nuclease domains and a single Tudor domain, which confer it endonuclease activity and extraordinary capacity for interacting with nucleic acids, individual proteins and protein complexes. Originally described as a transcriptional coactivator, SND1 plays fundamental roles in the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 101 publications
(151 reference statements)
0
32
1
Order By: Relevance
“…When blastospores were cultured under simulated conditions, the yield of blastospores was dramatically reduced in the Δ BbTdp1 mutant, indicating that BbTdp1 contributes to blastospore proliferation. In previous studies of oncogenes, SND1 was found to be highly expressed during the stage of malignant proliferation and aggressiveness of many common human cancer cells ( 10 ). In colon cancer, SND1 overexpression significantly accelerated cell proliferation in the exponential growth phase ( 31 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…When blastospores were cultured under simulated conditions, the yield of blastospores was dramatically reduced in the Δ BbTdp1 mutant, indicating that BbTdp1 contributes to blastospore proliferation. In previous studies of oncogenes, SND1 was found to be highly expressed during the stage of malignant proliferation and aggressiveness of many common human cancer cells ( 10 ). In colon cancer, SND1 overexpression significantly accelerated cell proliferation in the exponential growth phase ( 31 ).…”
Section: Discussionmentioning
confidence: 94%
“…Similar to other SND1 orthologs (e.g., TSN, Tudor-SN, and p100), BbTdp1 contains four SNc domains and one tudor domain. As a transcription coactivator, SND1 is considered to be involved not only in the regulation of gene expression, such as RNA splicing, interference, stability, and editing, but also in the control of protein and lipid homeostasis ( 10 ). In human cells, mature functional microRNAs (miRNAs) are degraded by SND1, which promotes the progression of the cell cycle, indicating that targeting SND1 nuclease activity could inhibit cell proliferation ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the work of Dubois et al, HSPA1A is present in the lipid rafts of prostasomes [24]. SND1 was first identified as a transcription coactivator [39] but has also been shown to have several functions related to RNA metabolism [40]. The expression of SND1 is increased in many cancers, including PrCa.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TGFβ signaling also induces SND1 transcriptional activation in a feed forward loop [ 140 ]. This feed forward activity can be seen in other SND1-regulated pathways including NF-κB and SREBPs [ 141 ]. SND1 further promotes proliferative signals by degradation of miRNA via its nuclease domains.…”
Section: Hallmarks Of Hccmentioning
confidence: 99%